2006
DOI: 10.1139/s05-030
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus uptake by cattail plants in a laboratory-scale experiment related to constructed treatment wetlands

Abstract: This paper describes a laboratory-scale study of phosphorus (P) uptake by broad-leaf cattail plants (Typha latifolia) growing in gravel substrate. The cattails were fed synthetic wastewater at P concentrations representative of primary and secondary municipal sewage effluent. Phosphorus uptake to the upper and lower portions of the cattail plants, adsorption to the gravel substrate, and the pore water concentration were measured over a simulated growing season. The objective was to quantify the mass of phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Higher P phytoextraction has been reported in other studies. For example, using synthetic wastewater in a laboratory‐constructed treatment wetland microcosm study, Weng et al (2006) reported 40 to 45% P removal by cattail plants growing in gravel substrate. Using model simulation, Mitsch and Wang (2000) estimated that 74% of P flowing into four constructed riparian wetlands along the Des Plaines River in Illinois was taken up by macrophytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher P phytoextraction has been reported in other studies. For example, using synthetic wastewater in a laboratory‐constructed treatment wetland microcosm study, Weng et al (2006) reported 40 to 45% P removal by cattail plants growing in gravel substrate. Using model simulation, Mitsch and Wang (2000) estimated that 74% of P flowing into four constructed riparian wetlands along the Des Plaines River in Illinois was taken up by macrophytes.…”
Section: Resultsmentioning
confidence: 99%
“…growing in a natural peatland receiving treated wastewater over a 30‐yr period. Weng et al (2006) reported 40 and 45% P removal by cattail grown in microcosms treating primary and secondary effluents, respectively.…”
mentioning
confidence: 99%
“…Naylor et al (2003) of the P mass input under the primary and secondary effluent conditions, respectively. Weng et al (2006) concluded that those results provide insight into the potential timing and effectiveness of cattail harvesting for removal of P from CW systems.…”
Section: Role Of Plants On Removal Efficiency: Canadian and Northern mentioning
confidence: 95%
“…response to N and P have relied on shoots produced from rhizome (root stalk), often of unknown history (e.g. Weng et al, 2006). The three studies located in the primary literature that propagated T. latifolia from seed (Ye et al, 1997;Wetzel and van der Valk, 1998;Kercher and Zedler, 2004) provided incomplete details on germination and propagation protocols.…”
Section: Overviewmentioning
confidence: 99%
“…Several studies have documented increased T. latifolia biomass in wetlands subjected to wastewater effluent or levels characteristic of wastewater entering constructed wetlands and drainages (e.g. Martín and Fernández, 1992;Weng et al, 2006;Maddison et al, 2009). Martín and Fernández (1992) documented a significant increase in T. latifolia biomass within a river channel receiving secondarily treated wastewater with mean concentrations of 6.4mg PO 4 -P/L, 11.6 mg NH 4 -N /L and 6.4mg NO 3 -N/L, which far exceeds hypereutrophic levels, as well as elevated levels of magnesium (Mg), potassium (K) and calcium (Ca).…”
Section: Typha Productivity In Wastewater and Constructed Wetlands Effluentmentioning
confidence: 99%